home | career | drupal | java | mac | mysql | perl | scala | uml | unix

Groovy example source code file (AssertionRenderingTest.groovy)

This example Groovy source code file (AssertionRenderingTest.groovy) is included in the DevDaily.com "Java Source Code Warehouse" project. The intent of this project is to help you "Learn Java by Example" TM.

Java - Groovy tags/keywords

arraylist, arraylist, assertionrenderingtest, groovytestcase, holder, holder, list, list, string, string

The Groovy AssertionRenderingTest.groovy source code

/*
 * Copyright 2008 the original author or authors.
 *
 * Licensed under the Apache License, Version 2.0 (the "License");
 * you may not use this file except in compliance with the License.
 * You may obtain a copy of the License at
 *
 *     http://www.apache.org/licenses/LICENSE-2.0
 *
 * Unless required by applicable law or agreed to in writing, software
 * distributed under the License is distributed on an "AS IS" BASIS,
 * WITHOUT WARRANTIES OR CONDITIONS OF ANY KIND, either express or implied.
 * See the License for the specific language governing permissions and
 * limitations under the License.
 */

package org.codehaus.groovy.runtime.powerassert

import static AssertionTestUtil.*
import static java.lang.Math.min

/**
 * Tests rendering of whole assertions.
 *
 * @author Peter Niederwieser
 */

class AssertionRenderingTest extends GroovyTestCase {
    void testSimpleAssertion() {
        isRendered """
assert x == 1
       | |
       2 false
        """, {
            def x = 2
            assert x == 1
        }
    }

    void testMultiLineAssertion() {
        isRendered """
assert 1 + 2 == 4 - 2
         |   |    |
         3   |    2
             false
        """, {
            assert 1 +
                2 ==



4 -

                          2

        }
    }

    private one(x) { 0 }

    void testMethodCallExpressionWithImplicitTarget() {
        isRendered """
assert one(a)
       |   |
       0   1
        """, {
            def a = 1
            assert one(a)
        }
    }

    void testMethodCallExpressionWithExplicitTarget() {
        isRendered """
assert a.get(b) == null
       | |   |  |
       | 1   0  false
       [1]
        """, {
            def a = [1]
            def b = 0
            assert a.get(b) == null
        }
    }

    void testMethodCallExpressionWithGStringMethod() {
        isRendered """
assert [1]."\$x"(0) == null
           | |     |
           1 get   false
        """, {
            def x = "get"
            assert [1]."$x"(0) == null
        }
    }

    void testMethodCallExpressionCallingStaticMethod() {
        isRendered """
assert Math.max(a,b) == null
            |   | |  |
            2   1 2  false
        """, {
            def a = 1
            def b = 2
            assert Math.max(a,b) == null
        }
    }

    void testMethodCallExpressionSpreadDot() {
        isRendered """
assert ["1", "22"]*.size() == null
                    |      |
                    [1, 2] false
        """, {
            assert ["1", "22"]*.size() == null
        }
    }

    void testMethodCallExpressionSafe() {
        isRendered """
assert a?.foo()
       |  |
       |  null
       null
        """, {
            def a = null
            assert a?.foo()
        }
    }

    void testStaticMethodCallExpression() {
        isRendered """
assert min(a,b) == null
       |   | |  |
       1   1 2  false
        """, {
            def a = 1
            def b = 2
            assert min(a,b) == null
        }
    }

    void testConstructorCallExpression() {
        isRendered """
assert new ArrayList(a) == null
       |             |  |
       []            1  false
        """, {
            def a = 1
            assert new ArrayList(a) == null
        }

    }

    void testTernaryExpression() {
        isRendered """
assert a ? b : c
       |   |
       1   0
        """, {
            def a = 1
            def b = 0
            def c = 1
            assert a ? b : c
        }

        isRendered """
assert a ? b : c
       |       |
       0       0
        """, {
            def a = 0
            def b = 1
            def c = 0
            assert a ? b : c
        }
    }

    void testShortTernaryExpression() {
        isRendered """
assert (a ?: b) == null
        |       |
        1       false
        """, {
            def a = 1
            def b = 2
            assert (a ?: b) == null
        }

        isRendered """
assert a ?: b
       |    |
       0    0
        """, {
            def a = 0
            def b = 0
            assert a ?: b
        }
    }

    void testBinaryExpression() {
        isRendered """
assert a * b
       | | |
       0 0 1
        """, {
            def a = 0
            def b = 1
            assert a * b
        }

        isRendered """
assert a[b]
       |||
       ||0
       |false
       [false]
        """, {
            def a = [false]
            def b = 0
            assert a[b]
        }
    }

    void testPrefixExpression() {
        isRendered """
assert ++x == null
       | | |
       1 0 false
        """, {
            def x = 0
            assert ++x == null
        }
    }

    void testPostfixExpression() {
        isRendered """
assert x++ == null
       ||  |
       |0  false
       0
        """, {
            def x = 0
            assert x++ == null
        }
    }

    void testBooleanExpression() {
        isRendered """
assert a
       |
       null
        """, {
            def a = null
            assert a
        }
    }

    void testClosureExpression() {
        isRendered """
assert { 1 + 2 } == null
                 |
                 false
        """, {
            assert { 1 + 2 } == null
        }
    }

    void testTupleExpression() {
        // TupleExpression is only used on LHS of (multi-)assignment,
        // but LHS of assignment is not rewritten
        isRendered """
assert ((a,b) = [1,2]) && false
              |        |
              [1, 2]   false
        """, {
          def a
          def b
          assert ((a,b) = [1,2]) && false
        }
    }

    void testMapExpression() {
        isRendered """
assert [a:b, c:d] == null
          |    |  |
          2    4  false
        """, {
            def b = 2
            def d = 4
            assert [a:b, c:d] == null
        }

        isRendered """
assert [(a):b, (c):d] == null
        |   |  |   |  |
        1   2  3   4  false
        """, {
            def a = 1
            def b = 2
            def c = 3
            def d = 4
            assert [(a):b, (c):d] == null
        }
    }

    void testListExpression() {
        isRendered """
assert [a,b,c] == null
        | | |  |
        1 2 3  false
        """, {
            def a = 1
            def b = 2
            def c = 3
            assert [a,b,c] == null
        }
    }

    void testRangeExpression() {
        isRendered """
assert (a..b) == null
        |  |  |
        1  2  false
        """, {
            def a = 1
            def b = 2
            assert (a..b) == null
        }

        isRendered """
assert (a..<b) == null
        |   |  |
        1   2  false
        """, {
            def a = 1
            def b = 2
            assert (a..<b) == null
        }
    }

    void testPropertyExpression() {
        isRendered """
assert a.size == null
       | |    |
       | 1    false
       [9]

        """, {
            def a = [9]
            assert a.size == null
        }

        isRendered """
assert Integer.MIN_VALUE == null
               |         |
               |         false
               -2147483648
        """, {
            assert Integer.MIN_VALUE == null
        }
    }

    void testAttributeExpression() {
        isRendered """
assert holder.@x
       |       |
       h       0
        """, {
            def holder = new Holder()
            assert holder.@x
        }
    }

    void testMethodPointerExpression() {
        isRendered """
assert a.&"\$b" == null
       |    |  |
       []   |  false
            get
        """, {
            def a = []
            def b = "get"
            assert a.&"$b" == null
        }
    }

    void testConstantExpression() {
        isRendered """
assert 1 == "abc"
         |
         false
        """, {
            assert 1 == "abc"
        }
    }

    void testClassExpression() {
        isRendered """
assert List == String
            |
            false
        """, {
            assert List == String
        }
    }

    void testVariableExpression() {
        isRendered """
assert x
       |
       0
        """, {
            def x = 0
            assert x
        }
    }

    void testGStringExpression() {
        isRendered '''
assert "$a and ${b + c}" == null
         |       | | |   |
         1       2 5 3   false
        ''', {
            def a = 1
            def b = 2
            def c = 3
            assert "$a and ${b + c}" == null
        }
    }

    void testArrayExpression() {
        isRendered """
assert new int[a][b] == null
               |  |  |
               1  2  false
        """, {
            def a = 1
            def b = 2
            assert new int[a][b] == null
        }
    }

    private two(a, b) { 0 }

    void testSpreadExpression() {
        isRendered """
assert two(*a)
       |    |
       0    [1, 2]
        """, {
            def a = [1, 2]
            assert two(*a)
        }

        isRendered """
assert [1, *a] == null
            |  |
            |  false
            [2, 3]
        """, {
            def a = [2, 3]
            assert [1, *a] == null
        }
    }

    void testSpreadMapExpression() {
        isRendered """
assert one(*:m)
       |     |
       0     [a:1, b:2]
        """, {
            def m = [a:1, b:2]
            assert one(*:m)
        }

        isRendered """
assert [a:1, *:m] == null
               |  |
               |  false
               [b:2, c:3]
        """, {
            def m = [b:2, c:3]
            assert [a:1, *:m] == null
        }
    }

    void testNotExpression() {
        isRendered """
assert !a
       ||
       |true
       false
        """, {
            def a = true
            assert !a
        }
    }

    void testUnaryMinusExpression() {
        isRendered """
assert -a == null
       || |
       |1 false
       -1
        """, {
            def a = 1
            assert -a == null
        }
    }

    void testUnaryPlusExpression() {
        isRendered """
assert +a == null
       || |
       |1 false
       1
        """, {
            def a = 1
            assert +a == null
        }
    }

    void testBitwiseNegationExpression() {
        isRendered """
assert ~a == null
       || |
       |1 false
       -2
        """, {
            def a = 1
            assert ~a == null
        }
    }

    void testCastExpression() {
        isRendered """
assert (List)a
             |
             null
        """, {
            def a = null
            assert (List)a
        }

        isRendered """
assert a as int[]
       |
       null
        """, {
            def a = null
            assert a as int[]
        }
    }

    private three(a,b,c) { 0 }

    void testArgumentListExpression() {
        isRendered """
assert three(a, b,c)
       |     |  | |
       0     1  2 3
        """, {
            def a = 1
            def b = 2
            def c = 3
            assert three(a, b,c)
        }
    }

    void testExplicitClosureCall() {
        def func = { it }

        isRendered """
assert func.call(42) == null
       |    |        |
       |    42       false
       ${func.toString()}
        """, {
            assert func.call(42) == null
        }
    }

    /*
    void testMapEntryExpression() {
        // tested as part of testMapExpression
    }

    void testFieldExpression() {
        // doesn't seem to be used
    }

    void testDeclarationExpression() {
        // cannot occur in an assertion statement
    }

    void testRegexExpression() {
        // doesn't seem to be used
    }

    void testClosureListExpression() {
        // cannot occur in an assertion statement
    }

    void testBytecodeExpression() {
        // cannot occur in an assertion statement
    }
    */
}

private class Holder {
    public x = 0
    def getX() { 9 }
    String toString() { "h" }
}

Other Groovy examples (source code examples)

Here is a short list of links related to this Groovy AssertionRenderingTest.groovy source code file:

new blog posts

 

Copyright 1998-2013 Alvin Alexander, alvinalexander.com
All Rights Reserved.